The Sociology of Knowledge as a Means of Studying Knowledge Production: A Review of Asian and Western Scholars - Azizan bin Had; Starry Garijih (2020)
This paper analyses the Sociology of Knowledge (SoK) proposed by Karl Mannheim (1893-1947) and other scholars to provide a modified theory to the study of knowledge production and the product. It is hoped that the study of SoK theory could lead to the formation of a theory that could objectively explain why a person, organization acted the way they are and how they obtain knowledge. The paper also seeks to discuss the importance of major SoK terminology and conception such as the concept of ideology, utopia, objective and subjective reality, and power/knowledge. Beside Mannheim, the SoK theory was also assumed and expanded by other scholars such as Peter Berger in his work The Social Construction of Reality (Berger & Luckmann 1991). Another scholar who had a corresponding vision as Mannheim is Michel Foucault in his work Archeology of Knowledge (1972), The Order of Things (1994) and Discipline and Punishment: The Birth of the Prison (1977).  The gradual interest in the theory of SoK in recent years can be identified in the works of Goldman (1994) who asserted how relevance Mannheim’s work to the social thought of modern times since it provides a detailed explanation of the causes, problems, and solutions to the theory of knowledge. Furthermore, Mannheim’s theory also offers a comprehensive explanation of how external factors define an individual’s thought (Drucker, 1972; Heeren, 1971; Tanner, 2009; Pels, 1997).  The farsightedness of Mannheim’s theory goes beyond the years of his time and is still applicable today. The work of Peter Berger focusing on how reality affects a person’s thought and Michel Foucault, who explains the origin of knowledge has mostly shifted scholarly attention towards the importance of SoK and the study of epistemology of knowledge and its relation to reality. Asian scholars were also obligated to Mannheim as they have applied his theory to explain the past and current events that are linked to the socio-historical situation of Southeast Asia. The late Prof. Syed Hussein Alatas, for example, used Mannheim’s theory to write his magnum opus entitled Myth of the Lazy Native: A Study of the Image of the Malays, Filipinos and Javanese from the 16th to the 20th Century and its Function in the Ideology of Colonial Capitalism (1977b) which reveals colonial ideologies (a term used by Mannheim to refer to false knowledge or lies) in developing Southeast Asian nations.